The child as a player and his/her special reading games: for an analysis of optical illusions books - Silva, Sara Raquel Reis da (2017)
Optical illusion books belong to the category of object-books and of movable books, whose main feature is interactivity with the reader. Also known as action books or special effects books, these texts invite to participate in a special reading game. Intentionally playful, they compel readers to question models of reading. This study aims at deepening a critical reflection on these books, by analysing, using textual techniques of analysis from the scope of narratology, six examples, all recently edited and selected for their aesthetic quality and innovative character: Isto ou Aquilo? [This or That?], by Dobroslav Foll; Olá Adeus [Hello Goodbye], by Delphine Chedru; Veo Bichos [I see animals], by Cintia Martín; and Nova Iorque em Pijamarama [New York in Pyjamarama], Luna Parque em Pijamarama [Luna Park in Pyjamarama], and Os Meus Robôs em Pijamarama [My Robots in Pyjamarama], by Michael Leblond and Frédérique Bertrand. These books provide an acetate overlay for transforming illustrations. Most also have a grid to slide over the pages to produce new images. Some have a narrative, while others are just a visual sequence representing several objects, human figures or nature elements. These books surprise, require trained perception and interpretation skills. By responding to the child’s ludic impulse, as well as contributing to increase concentration power and stimulating their imagination, these “participation books” become aesthetically and intellectually captivating.